Recently recycled synaptic vesicles use multi-cytoskeletal transport and differential presynaptic capture probability to establish a retrograde net flux during ISVE in central neurons - Parkes, Mason; Landers, Nathan L.; Gramlich, Michael W. (Frontiers in Cell and Developmental Biology, 2023)
Presynapses locally recycle synaptic vesicles to efficiently communicate information. During use and recycling, proteins on the surface of synaptic vesicles break-down and become less efficient with use over time. In order to maintain efficient presynaptic function and accommodate protein break-down, new proteins are regularly produced in the soma and trafficked to presynaptic locations where they replace older protein carrying vesicles. Maintaining a balance of new protein and older protein is thus essential for presynaptic maintenance and plasticity. While protein production and turnover have been extensively studied, it is still unclear how older synaptic vesicles are trafficked back to the soma for recycling in order to maintain balance. In the present study, we use a combination of fluorescence microscopy, hippocampal cell cultures, and computational analyses to determine the mechanisms that mediate older synaptic vesicle trafficking back to the soma. We show that synaptic vesicles, which have recently undergone exocytosis, can differentially utilize either the microtubule or the actin cytoskeleton networks. We show that axonally trafficked vesicles travelling with higher speeds utilize the microtubule network and are less likely to be captured by presynapses, while slower vesicles utilize the actin network and are more likely to be captured by presynapses. We also show that retrograde driven vesicles are less likely to be captured by a neighboring presynapse compared to anterograde driven vesicles. We show that loss of synaptic vesicle bound molecular motor myosin-V is the mechanism that differentiates whether vesicles will utilize the microtubule or actin networks. Finally, we present a theoretical framework of how our experimentally observed retrograde vesicle trafficking bias maintains the balance with previously observed rates of new vesicles trafficking from the soma.